2017
DOI: 10.1177/1010428317698370
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptors in breast cancer

Abstract: Fibroblast growth factor receptors are growth factor receptor tyrosine kinases, exerting their roles in embryogenesis, tissue homeostasis, and development of breast cancer. Recent genetic studies have identified some subtypes of fibroblast growth factor receptors as strong genetic loci associated with breast cancer. In this article, we review the recent epidemiological findings and experiment results of fibroblast growth factor receptors in breast cancer. First, we summarized the structure and physiological fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Consistent with our observation, Roidl et al showed that FGFR4 gene expression is up-regulated in doxorubicin-treated, apoptosis resistant cancer cell clones [37]. Activating FGFR4 can inhibit the MAPK, PI3K/Akt or NF-κB signaling pathway depending on the cellular context [21, 24]. In this study, we observed drastic changes of Erk1/2 phosphorylation in ADR-R cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with our observation, Roidl et al showed that FGFR4 gene expression is up-regulated in doxorubicin-treated, apoptosis resistant cancer cell clones [37]. Activating FGFR4 can inhibit the MAPK, PI3K/Akt or NF-κB signaling pathway depending on the cellular context [21, 24]. In this study, we observed drastic changes of Erk1/2 phosphorylation in ADR-R cells.…”
Section: Discussionsupporting
confidence: 79%
“…The binding of FGFR4s to the corresponding FGF ligands causes receptor dimerization and transphosphorylation of FGFR tyrosine domains [21-23]. Activated FGFR phosphorylates FGF receptor substrate 2 (FRS2) and leads to the activation of downstream signaling pathways, including MAPK, PI3K/AKT, and NF-κB [15, 18, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent reports suggest that FGFR3 may participate in a molecular pathway leading to breast cancer development. This fact indicates that the FGFR3 protein might be a target to be considered in FGFR3-related breast cancer 63 . FIGF is related with tumor cell migration in colorectal cancer metastasis 64 .…”
Section: Discussionmentioning
confidence: 96%
“…IGF-I promotes tumor cell proliferation, malignant transformation, development of new vessels and tumor development 62 . FGFR3 high levels directly correlate with poor prognosis in mammary tumors 63 . Additionally, recent reports suggest that FGFR3 may participate in a molecular pathway leading to breast cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…FGF ligand binding to the FGFR caused receptor dimerization, transphosphorylation and activation of an intracellular tyrosine kinase domain (25). FGFR1 binds to the ligand FGF to activate the PI3K-AKT, IP3-PLC/DAG, JAK-STAT (26) and other signaling pathways which regulate cell self-renewal, metabolism, proliferation, EMT and angiogenesis (27,28). Recent studies revealed that the FGFR family, especially FGFR1, was abnormally highly expressed in a variety of tumor tissues like prostate, pancreatic and cervical cancer, as well as gliomas (29) (Fig.…”
Section: Discussionmentioning
confidence: 99%